Microwave Dielectric Properties of Ca1+xCu3Ti4O12+x (-0.04 ≤ x ≤ 0.04) Ceramics - M. J. Abu; M. F. Ab. Rahman; R.A. Zaman; M. Ahmadipour; J. J. Mohamed; M. F. ain; Z. A. Ahmad (Elsevier, 2016)
Ca1+xCu3Ti4O12+x (-0.04 ≤ x ≤ 0.04) ceramics were prepared by using conventional solid-state route. The microwave dielectric properties of the samples were investigated as a function of measured frequency and the Ca content. A pure perovskite structure was obtained for samples with -0.02 ≤ x ≤ 0.02, whereas small amount of CuO and CaTiO3 appeared in the samples with x = -0.04 and 0.04, respectively, indicated that the solubility limit of Ca atom in CCTO lattice was reached for this system. Adjusting of Ca content showed a little influence on the microstructure of the ceramics. The sample with x = 0 exhibited good microwave dielectric permittivity (ɛ’ ∼ 85), which nearly constant at a broad frequency range of 1 – 35 GHz, then abruptly dropped to ∼70 at 50 GHz. The other samples showed a strongly frequency dependence of dielectric permittivity from ∼100 (at 1 GHz) to ∼10 (at 50 GHz). The dielectric loss (tan-δ) for nonstoichiometry CCTO samples is relatively higher at least an order of magnitude and displays strong frequency dependence as compared with the x = 0 sample. The existence of vacancy (oxygen and Ca) and Ca/Cu disorder are the main factor affecting ɛ’ and tan-δ values of the ceramics.